2023
DOI: 10.1002/lary.30619
|View full text |Cite
|
Sign up to set email alerts
|

Social Media Utilization in Otolaryngology: A Scoping Review

Abstract: ObjectiveSocial media (SM) is an increasingly popular medium for the medical community to engage with patients, trainees, and colleagues. This review aimed to identify reported uses of SM in otolaryngology‐head and neck surgery (OHNS), assess the quality of evidence supporting these uses, and identify gaps in the literature. With the relative lack of regulatory guidelines for the development of SM content, we hypothesized that the quality of content available on SM would be highly variable.Data Sources and Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 179 publications
0
5
0
Order By: Relevance
“…We appreciate Mr. Muecke's thoughtful Letter to the Editor regarding our manuscript "Social Media Utilization in Otolaryngology: A Scoping Review." 1 We agree the growth and evolution of social media continue to present new challenges for clinicians and researchers, particularly regarding the dissemination of accurate medical information.…”
Section: Dear Editormentioning
confidence: 90%
“…We appreciate Mr. Muecke's thoughtful Letter to the Editor regarding our manuscript "Social Media Utilization in Otolaryngology: A Scoping Review." 1 We agree the growth and evolution of social media continue to present new challenges for clinicians and researchers, particularly regarding the dissemination of accurate medical information.…”
Section: Dear Editormentioning
confidence: 90%
“…This study was the first cross‐sectional descriptive analysis of otolaryngology‐related content on the video‐sharing app TikTok. Previous studies have identified the presence of OHNS content on other social media platforms; however, they do not include TikTok 9 . Facial plastic and reconstructive surgeons made up nearly half of the identified TikTok accounts, followed by general otolaryngology and minimal representation of laryngology, rhinology, otology, and pediatric otolaryngology.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified the presence of OHNS content on other social media platforms; however, they do not include TikTok. 9 Facial plastic and reconstructive surgeons made up nearly half of the identified TikTok accounts, followed by general otolaryngology and minimal representation of laryngology, rhinology, otology, and pediatric otolaryngology. The disproportionate representation of facial plastic and reconstruction accounts may be due to their use of TikTok to promote cosmetic private practice, which is consistent with the documented presence of general plastic surgery on the platform.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We read a recently published review article by Huang et al, which provides insights into the use of social media as a tool to share peer-reviewed otolaryngology-head and neck surgery (OHNS) research, with great interest. 1 We feel it is necessary to consider the implications of ongoing modifications to Twitter on the dissemination of peer-reviewed OHNS research following the commencement of Elon Musk as the Chief Executive Officer (CEO). 2 Previously, a "blue tick" was afforded to notable Twitter accounts of public interest or those with a high following count.…”
mentioning
confidence: 99%